Primary Murine Microglia are Resistant to Nitric Oxide Inhibition of Indoleamine 2, 3 Dioxygenase - Wang, Yunxia (2010)
Indoleamine 2,3-dioxygenase (IDO) is an intracellular heme containing enzyme that is activated by proinflammatory cytokines, including interferon-γ (IFNγ), and metabolizes tryptophan along the kynurenine pathway. Activation of murine macrophages induces not only IDO but also nitric oxide synthase (iNOS), and the ensuing production of nitric oxide (NO) inhibits IDO. To determine the sensitivity of primary cultures of murine microglia to NO, microglia were stimulated with recombinant murine IFNγ (1 ng/ml) and lipopolysaccharide (LPS) (10 ng/ml). This combination of IFNγ + LPS synergized to produce maximal amounts of nitrite as early as 16 h. Steady-state mRNAs for both iNOS and IDO were significantly increased by IFNγ + LPS at 4 h post-treatment, followed by an increase in IDO enzymatic activity at 24 h. Murine microglia (> 95% CD11b(+)) were pretreated with the iNOS inhibitor, L-NIL hydrochloride, at a dose (30 μM) that completely abrogated production of nitrite. L-NIL had no effect on IDO mRNA at 4 h or IDO enzymatic activity at 24 h following stimulation with IFNγ + LPS. These data establish that IDO regulation in murine microglia is not restrained by NO, thereby permitting the accumulation of kynurenine and its downstream metabolites in the central nervous system.